The Efficacy of the "Pojok Ceria" Interactive Bulletin Board in Enhancing Early Number Sense and Self-Directed Learning among First-Grade Students - Setiawan, Yohana; Marwa, Keterina; Borom, Alfian; Mamji, Yulianus (Journal of Integrated Elementary Education, 2025)
​This study aims to develop and examine the efficacy of the “Pojok Ceria” (Joyful Corner) interactive bulletin board in addressing the ongoing problems of low student engagement, weak development of early number sense, and limited self-directed learning in primary-level mathematics classes. This study employed a strong R&D framework that combines the development stages model proposed by Sukmadinata with principles of systematic instructional design from the ASSURE model. This study employed a qualitative approach that spanned over two months among the first-grade students of a public school in Indonesia. Through triangulation of observations in the classroom, analysis of student work, and video recordings, combined with Focus Group Discussions (FGDs) for more in-depth insight into a specific issue. This study indicated that the “Pojok Ceria”, designed with interactive activities, manipulatives, and interesting visuals, had a high intervention and practical value and was well accepted by the teachers in terms of usability. Additionally, the Interactive Bulletin Board has proven to be highly effective in promoting student involvement and fostering independent learning. At the same time, it is also effective in exploring number sense concepts among first-graders. These findings provide informative guideposts for effectively developing and implementing engaging learning environments that function well, especially in low-resource educational environments. Although the small sample size limits this study, it suggests a conclusive possibility of interactive media being produced locally. Hence, more longitudinal studies with larger and more diverse samples are needed to confirm and fully generalize the positive consequences.